Vocal (Vocabulary Adventure Land) Board Game Learning Media for Elementary School Students - Andini Puspita Sari; Sri Utami Dewi (STKIP PGRI Trenggalek, 2021)
The design of this research is R & D as one of the research design which aimed at developing educational products. Also, this study used quasi-experimental research to collect the data. The fifth-grade student of MI AL Huda Rejowinangun consisted of 27 students of 5A; 13 of male and 14 female students, also 26 students of 5B; 15 male and 11 female students. The instruments used are questionnaire, interview and test. The data collected by questionnaire is analyzed quantitative way, meanwhile, the interview is analyzed qualitative way. The result of need analysis score was 2443 that means the student agree that board game with vocabulary material needs to be a learning media. The result of field-testing was 2381 that means student agree that the product of this research was good and feasible to use as media in learning vocabulary. The result of the test; the sig. (2-tailed) showed 0.000 < 0.05 in the Post-test result which the basic rules of making an Independent sample t-test, it can be concluded that H0 is rejected meanwhile Ha is accepted. Considering the findings of the research, it is concluded that Vocal board game is an effective learning media to use for elementary school students especially for vocabulary mastery.